Online Catalogue Demonstration - DESIDOC, Director (DESIDOC Journal of Library & Information Technology, 2002)
A demonstration of online catalogue was organized by DESIDOC at its new building at Metcalfe House, Delhi, on 8 March 1988.Some of the prominent information scientists of Delhi attended the demonstration. Among those who witnessed the demonstration were: Shri SC Biswas, Director Central Secretariat library; Smt SL Chinnappa, Coordinator, NICICMR Centre for Biomedicals; Shri PC Bose, Information Systems Officer, ICAR; Shri VB Nanda, Librarian JNU; Shri AS Wahid, National Institute of Science Technology & Development Studies (CSIR); and Shri HK Kaul, Librarian, India International Centre.